Capability and Resources in Reaching Advantages of Competition of Small and Medium Enterprises - Suwignyo Widagdo; Emy Kholifah R; Yuniorita Indah Handayani (Future Science)
This article aims to look at the effect of capabilities and resources of small and medium businesses on competitive advantage. The writing of this article is based on the phenomenon that most small and medium businesses still have limited ability to achieve competitive advantage. This is due to the capabilities and resources that are also still not fully met. The analysis used to discuss this conceptual article is descriptive qualitative analysis. Capabilities include product quality and reputation while resources include the reliability of human resources, the ability to produce quality products and good teamwork. Competitive advantage is reflected by the uniqueness, reliable strategy and corporate value. The results of the discussion in this article indicate that capabilities and resources that reflect resources based view will affect the achievement of competitive advantage in small and medium businesses.